Goodnight Mister Tom - Magorian, Michelle (Puffin London, 2011)
Young Willie Beech is evacuated to the country as Britain stands on the brink of WW2. A sad, deprived child, he slowly begins to flourish under the care of old Tom Oakley - but his new-found happiness is shattered by a summons from his mum back in London